Queer-haptic aesthetics in the films of Lucrecia Martel and Albertina Carri. Issue 1 (1st March 2017) - Molloy, Missy
Lucrecia Martel and Albertina Carri are contemporaneous Argentine directors whose films are frequently included in the category 'New Argentine Cinema'. Often interpreted as indictments of bourgeois cultural values, Martel's La ciénaga/The Swamp (Martel, 2001), La niña santa/The Holy Girl (Martel, 2004) and La mujer sin cabeza/The Headless Woman (Martel, 2008) spotlight sexual, racial and economic inequalities that manifest in unconventional desires and sudden violence. Although more explicitly sexual and violent, Géminis/Geminis (Carri, 2005) and La rabia/Anger (Carri, 2008) similarly undermine heteronormative social conventions, the former film depicting sibling incest and the latter displacing idealized representations of rural life with images of sexual deviance and animal cruelty. This article presents haptic and queer analyses of these filmmakers' works to reveal overlaps in their sociopolitical critiques. The interpretations also demonstrate the utility of queer-haptic cinematic strategies, through which Martel and Carri expose alternative vantages on queer desires.